EMPLOYEE SALARY SLIPMAKING APPLICATIONS USING VISUAL BASIC 6.0 ON PT. WATSON WYATT PURBAJAGA - Slamet Prianto; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2004)
Given the increasingly sophisticated technology and the development of more advanced age, many institutions in the use of computers or the company has problems in terms of cost, especially concerning the payment of employee salaries. Hopefully with a more advanced technology and backed by good human resources, as well as hardware and software that is used as a tool to settle an issue that arises, the writer tries to create an MS-Windows based application that aims to help employees finance section in making a paycheck, and used to support decision-making for a leader.